2019
DOI: 10.17222/mit.2018.184
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of machining parameters in turning of hybrid aluminium-matrix (LM24–SiCp–coconut shell ash) composite

Abstract: In any machining process, the vital part is determination of the optimum values for the process parameters to attain the highest desired quality at a low machining cost. This paper mainly focuses on the surface-roughness optimization in the turning of a hybrid aluminium-matrix (LM24-SiCp-coconut shell ash) composite through the Taguchi method and a genetic algorithm. All composite samples for the study were prepared under the optimal squeeze-casting conditions and experimental trials were selected based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Replications were made for the experimental Runs 6, 7, and 8. The experimental Run 6 was repeated to estimate experimental error; the Run 7 was repeated since it uses high space velocity, low purge volume to feed volume ratio, long cyclic rate, and short bed length that will result in a relatively high dew point that is more sensitive to slight changes in operating conditions (Arulraj & Palani, ; Arulraj, Palani, & Venkatesh, ; Sowrirajan, Mathews, & Vijayan, ). The results summary for all the runs is presented in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Replications were made for the experimental Runs 6, 7, and 8. The experimental Run 6 was repeated to estimate experimental error; the Run 7 was repeated since it uses high space velocity, low purge volume to feed volume ratio, long cyclic rate, and short bed length that will result in a relatively high dew point that is more sensitive to slight changes in operating conditions (Arulraj & Palani, ; Arulraj, Palani, & Venkatesh, ; Sowrirajan, Mathews, & Vijayan, ). The results summary for all the runs is presented in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Different optimization techniques have been used, which includes TOPSIS, GA, Promethee, AHP and so on. Many of the researches [19][20][21][22] have been carried out considering hybridization of algorithms such as Taguchi design along TOPSIS, GA along with fuzzy grey relation and grey fuzzy analysis. Better and most widely used optimization techniques are applied for various optimization problems of casting process.…”
Section: Optimization Techniquesmentioning
confidence: 99%
“…The benefits of adding agro waste are low cost, ease of access, low density and reduced pollution. Agro waste like ground nut shell ash (GSA) , bamboo leaf ash(BLA), rice husk ash (RHA), bagasse ash, palm kernel shell ash, maize stalk ash, corn cob ash (CCA), bean shell waste ash etc are researched and promising results have been reported [32][33][34][35][36][37][38][39][40][41][42][43][44]. Fatile OB et al have reported by adding the corn cob with SiC has no significant rise of porosity but while increasing the percentage of corn cob reduces the mechanical properties gradually.…”
Section: Introductionmentioning
confidence: 99%
“…The elements present in CDA ash are SiO 2 , Al 2 O 3 , Fe 2 O 3 , MgO etc which could enhance the properties of aluminium. The benefits of adding CDA are low cost, ease of access, low density and reduced pollution [34][35][36][37][38][39][40][41]. Hence an attempt has been made in reinforcing CDA as second reinforcement in the matrix.…”
Section: Introductionmentioning
confidence: 99%